Expression Level Dominance and Homeolog Expression Bias Upon Cold Stress in the F1 Hybrid Between the Invasive Sphagneticola trilobata and the Native S. calendulacea in South China, and Implications for Its Invasiveness - Wu, Wei; Guo, Wei; Ni, Guangyan; Wang, Longyuan; Zhang, Hui; Ng, Wei Lun (Frontiers in Genetics, 2022)
The role of hybridization is significant in biological invasion, and thermotolerance is a trait critical to range expansions. The South American Sphagneticola trilobata is now widespread in South China, threatening the native S. calendulacea by competition and hybridization. Furthermore, upon formation, their F1 hybrid can quickly replace both parents. In this study, the three taxa were used as a model to investigate the consequences of hybridization on cold tolerance, particularly the effect of subgenome dominance in the hybrid. Upon chilling treatments, physiological responses and transcriptome profiles were compared across different temperature points to understand their differential responses to cold. While both parents showed divergent responses, the hybrid’s responses showed an overall resemblance to S. calendulacea, but the contribution of homeolog expression bias to cold stress was not readily evident in the F1 hybrid possibly due to inherent bias that comes with the sampling location. Our findings provided insights into the role of gene expression in differential cold tolerance, and further contribute to predicting the invasive potential of other hybrids between S. trilobata and its congeners around the world.